At the end of the road: is there life after rolling? Life cycle assessment of the impacts of different end of life treatments of tyres - Anchustegui, Pedro; Pasakopoulos, Efstathios (My University, 2019)
End of life tyres (ELTs) are waste in the form of passenger car tyres that are no longer suitable to perform their original function. As such, this waste must be disposed of in compliance with European legislation, which forbids them to be landfilled and at the same time encourages them to be recovered or recycled with the End of Life Vehicle Directive. This study is performed for Volvo Car Corporation to map out the Swedish ELT treatment system and, by performing a life cycle assessment, quantify the impacts of the system. An additional goal was to analyze which of all the fates in the treatment of tyres is less impactful from an environmental perspective. The objective of this report is to analyze the fates of ELTs and their impacts in Sweden. The increasing environmental concern which eventually turns into legislation puts pressure on companies to acquire knowledge for the environmental impacts of their products. The method of this study is LCA and it is performed from gate to grave. It is a method to assess the environmental impacts related to a product or a service. The stages that were taken into account were the use of energy, resources, water and transportation. The results are presented in the form of different impact categories which gives a broader perspective in the environmental attribute. LCA can be used for detecting improvement possibilities and mapping all the different processes in a system not studied as a whole, and calculate their impacts, which is what is done in this study. The system was mapped and the four main fates were found to be: incineration of ELTs as fuel in the clinker production, with 40.4% of the share per weight; incineration in coal furnaces for the production of metallurgical coke, with 32% of the share per weight; separation into rubber, steel and textile fractions, as 12% of the share per weight; and pyrolysis with 5% of the share per weight. The impact assessment shows that the incineration of ELTs as fuel in both coal furnaces and clinker production contribute the most to the overall impact of the system. When a system expansion is done, however, the credits from avoiding the production and incineration of fossil fuels paints a different picture on the role of ELTs play in the system as a viable replacement of fossil fuels in energy intensive processes. Pyrolysis was found to be the best treatment option for ELTs from an environmental standpoint, and a sensitivity analysis was performed to evaluate the change in the overall impacts of the system with an increase in the pyrolysis share. The sensitivity analysis confirmed that an increased percentage of pyrolysis in the system would lower its overall emissions.
Keywords: ELT; tyres; end of life; end of life tyres; ELV; end of life vehicles; life cycle assessment; LCA